ASSESSING PREVALENCE AND FACTORS ASSOCIATED WITH CESAREAN DELIVERY AMONG WOMEN OF REPRODUCTIVE AGE IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Cesarean section (CS) involves the fetus, membranes, and placenta delivery through abdominal and uterine incisions after fetal viability. Some research on CS use in Nigeria have been undertaken, however, they have all been institutional-based and had small sample sizes. In the country, nationally representative studies on this critical issue are required. As a result, the current study assesses prevalence and factors associated with cesarean delivery among women of reproductive age in Nigeria. The data used in this study were sourced from the 2018 Nigeria Demographic and Health Survey (NDHS). 8216 women of childbearing age were considered in this study. The 2018 survey is the most recent in Nigeria's series of NDHS (at the time of this study). The methods of analysis used for this study are frequency, percentage, chi-square test, and Binary Logistic Regression Analysis. Statistical software used for the analysis was STATA V.15. p
Keywords: Cesarean section; prevalence; women; reproductive age; Nigeria